THE USE OF PERSONAL PHOTOGRAPH IN TEACHING DESCRIPTIVE TEXT WRITING TO MTsN - Hidayati, Reski; Apriliaswati, Rahayu; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of conducting this research is to know whether or not the use of personal photograph is effective to teach students’ ability in descriptive text writing and how effective the use of personal photograph to teach students’ ability in descriptive text writing at the seventh grade students of MTsN Jongkong in academic year 2015/2016. This research was done by conducting a pre- experimental study which consists of pretest, two times of treatments and posttest. The sample of this research is class VII Aand consists of 40 students.The data had been collected by measurement technique with pre-test and post-test. The tool of data collecting is written test.The result of the mean score in pre-test is 33.91 and the students mean score in post-test is 56.52. The interval score from pre-test and post-test is 22.61. It means that the students’ score increased from pre-test to post-test. Based on the computation of t-test it showed that t-test was higher that t-table (3.29>2.074).Besides that, based on the computation of the effect size, it showed that the effect of the treatment is 0.658 this score categorized as moderate. It means that personal photograph is average for teaching descriptive text writing of MTsN Jongkong in academic year 2015/2016. Key words: Personal Photograph, Descriptive Text Writing Abstrak: penelitian ini bertujuan untuk mengetahui apakah penggunaan personal photograph effektip untuk mengajar kemampuan siswa dalam menulis teks deskriptif dan seberapa effektip penggunaan personal photograph untuk mengajar kemampuan siswa dalam menulis teks deskriptif pada siswa kelas tujuh MTsN Jongkong pada tahun ajaran 2015/2016.Penelitian ini dilakukan dengan menerapkan pre-experimental study yang terdiri dari pretest, dua kali treatments dan posttest. Sampel dalam penelitian ini adalah iswa kelas tujuh A dan terdiri dari 40 siswa. Data yang dikumpulkan menggunakan teknik pengumpulan data melalui pretest dan posttest. Alat pengumpulan data adalah tes tertulis. Hasil dari rata-rata skor pada pretest adalah 33.91 dan skor rata-rata pada posttest adalah 56.52. rentangan skor dari pretest dan posttest adalah 22.61. hal tersebut berarti skor siswa meningkat dari pretest ke posttest. Berdasarkan perhitungan t-test menunjukkan bahwa t-test lebih tinggi dari pada t-table (3.29>2.074). Selain itu berdasarkan perhitungan dari effect size menunjukkan bahwa efek dari treatment adalah 0.658 skor ini dikategorikan sebagai sedang. Hal ini berarti personal photograph efektif untuk mengajar menulis teks deskriptif pada MTsN Jongkong pada tahun ajaran 2015/21016. Key Words: Personal Photograph, Menulis Teks Deskriptif